Contrasting influences on bacterial symbiont specificity by co-occurring deep-sea mussels and tubeworms - Goffredi, Shana; Brzechffa, Camille (Dryad, 2020)
Relationships between deep-sea invertebrates and bacterial symbionts,
fueled by sulfide and methane, are well known, yet factors influencing
symbiont specificity remain cryptic. For animals that obtain their
symbionts from the environment, both host identity and geographic location
can impact the ultimate symbiont partner. Bacterial symbionts were
analyzed for 3 co-occurring species each of Bathymodiolus mussels and
vestimentiferan tubeworms, from three deep methane seeps off the west
coast of Costa Rica. The bacterial internal transcribed spacer gene was
analyzed via direct and barcoded amplicon sequencing to reveal fine-scale
symbiont diversity. Each of the three mussel species (B. earlougheri, B.
billschneideri and B. nancyschneideri) hosted genetically-distinct
thiotrophic endosymbionts, despite living nearly side-by-side in their
habitat, suggesting that host identity is influential in driving symbiont
specificity. The dominant thiotrophic symbiont of co-occurring tubeworms
Escarpia spicata and Lamellibrachia (L. barhami and L. donwalshi), on the
other hand, was identical regardless of host species or sample location,
suggesting lack of influence by either factor on symbiont selectivity in
this group of animals. These findings highlight the specific, yet
distinct, influences on the environmental acquisition of symbionts in two
foundational invertebrates with similar lifestyles, and provide a rapid
and precise method of examining symbiont identities.
Three co-occurring mussel species (B. earlougheri, B. billschneideri and
B. nancyschneideri) and co-occurring vestimentiferans, Escarpia spicata
and two species of Lamellibrachia (L. barhami and L.
donwalshi), were sampled from three methane seep sites in 2017
and 2018 ranging from 990m-1742 m depth off the west
coast of Costa Rica (Quepos Seep, Mound 12, Jaco Scar). Mound 12 (8°
55.794N / 84° 18.780W), Jaco Scar (9° 7.071N / 84° 50.445W), and Quepos
Seep (9° 1.904N / 84° 37.294W).  Total genomic DNA was extracted
from symbiont-bearing tissues using the Qiagen DNeasy kit (Qiagen,
Valencia, CA, USA) according to the manufacturer’s
instructions. A ~400bp region of the ITS gene was amplified using
primers with Illumina adapters on the 5′ end Sym-ITS-1322F
(5′- TCGTCGGCAGCGTCAGATGTGTATAAGAGACAGGTTGGAATCGCTAGTAATCG-3′)
and Sym-ITS-356R
(5′-GTCTCGTGGGCTCGGAGATGTGTATAAGAGACAGGACCAGGCCGACAACGCAGT-3′; according
to Won et al. 2003), and an annealing temperature of 54°C for 25 cycles,
and further following the details in Goffredi et al. 2020. Data was
processed in Quantitative Insights Into Microbial Ecology (v1.8.0) Direct
16S rRNA sequencing was accomplished using the 27F-1492R primer pair.
Direct ITS sequencing was accomplished using the Sym-ITS-1322F /
Sym-ITS-356R primer pair without the Illumina adapters (underlined above).